Preparation method of catalyst for synthesis of high-activity bio-based polyol
Through the new catalyst preparation method, the catalyst with comb-shaped chain structure and complex metal ions are used to coordinate catalysis, and the problem of chain breakage caused by reaction between catalyst and ester group in the prior art is solved, and the high-reactive bio-based polyether polyol is realized. High primary hydroxyl content and narrow molecular weight distribution improve product performance.
Patent Information
- Application Number
- CN202411288289.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-13
AI Technical Summary
When existing catalysts catalyze the synthesis of highly active bio-based polyols, they are prone to react with ester groups to cause chain breakage, resulting in the primary hydroxyl content of the polyether polyol is less than 80%, and the molecular weight distribution becomes wider, affecting product performance.
Using a new catalyst preparation method, by mixing the ligand polymer with alcohol compounds and reacting synchronously with potassium hexacyanocobaltate aqueous solution and zinc brine solution, a solid precipitate is formed, which is washed and desalted by weak acid. A catalyst with a comb-shaped chain structure is obtained, and the ring opening reaction of ethylene oxide is synergistically catalyzed with complex metal ions.
The synthesis of highly reactive bio-based polyether polyols has been achieved, with primary hydroxyl content above 80%, and ester-based chain breakage. It has the advantage of narrow molecular weight distribution, which improves the application performance of the product.
Smart Images

Figure BDA0005043728740000021 
Figure BDA0005043728740000041 
Figure BDA0005043728740000042
Abstract
Description
Technical Field
[0001] The invention belongs to the field of catalyst synthesis, and in particular, relates to a method for preparing a catalyst for synthesizing highly active bio-based polyols. Background Art
[0002] High resilience foam is a soft polyurethane foam with excellent resilience performance, which is widely used in furniture, vehicle seats, experience equipment and other fields. The preparation of high resilience foam uses high-activity polyether polyol and isocyanate as the main raw materials, among which high-activity polyether polyol is an EO-terminated polyether polyol product with a primary hydroxyl content of >80%. The high primary hydroxyl content provides high reactivity between polyether and isocyanate.
[0003] The development of vegetable oil polyols is considered to be an effective way to develop bio-based materials. It is derived from vegetable oil as raw material through chemical modification of molecular structure. It is an important renewable resource. It reacts with isocyanate compounds to form polyurethane and is a good substitute for petroleum-based polyols. The hydroxyl functionality of castor oil is 2.7, which meets the application requirements of soft foam polyether polyols and is an ideal initiator for soft foam polyethers. Patents CN10112 1784A and CN103694465A disclose a preparation method for synthesizing castor oil-based polyether polyols using DMC catalysis. However, DMC catalyst is not suitable for the polymerization catalysis of pure ethylene oxide, so the primary hydroxyl content of the prepared bio-based polyether polyol is far less than 80%. Alkali metal catalysts such as potassium hydroxide can catalyze the polymerization of PO and EO, but the reaction of alkali metal catalysts with ester groups in castor oil causes chain scission, and the molecular weight distribution of the obtained polyether polyol becomes wider, affecting the application performance of the final product.
[0004] In summary, it is crucial to develop a catalyst that can overcome the above problems and is suitable for the synthesis of highly active castor oil polyether polyols. Summary of the invention
[0005] In view of the problems existing in the above-mentioned prior art, the object of the present invention is to provide a method for preparing a catalyst for the synthesis of highly active bio-based polyols. The catalyst prepared by the method of the present invention can realize EO catalytic polymerization to prepare highly active bio-based polyether polyols, and will not react with ester groups to cause chain scission, and has the advantage of a narrow molecular weight distribution.
[0006] To achieve its purpose, the present invention adopts the following technical solutions:
[0007] A method for preparing a catalyst for synthesizing highly active bio-based polyols comprises the following steps:
[0008] 1) mixing the ligand polymer and the alcohol compound to obtain a catalyst ligand;
[0009] 2) the catalyst ligand obtained in step 1) and the potassium hexacyanocobaltate aqueous solution are simultaneously and slowly added dropwise to the zinc salt aqueous solution to react, and a solid precipitate is obtained as a crude catalyst;
[0010] 3) The crude catalyst is washed with a weak acid aqueous solution, then washed with desalted water, filtered to remove water, and then post-processed to obtain the catalyst.
[0011] According to the preparation method of the present invention, in step 1), the structure of the ligand polymer is:
[0012]
[0013] Among them, a:b=10:1-20:1, a:c=1:1-1:3, 50≤m+n≤100, m:n=1:1-1:10.
[0014] According to the preparation method of the present invention, in step 1), the alcohol compound is one or more of isopropanol, tert-butanol, propylene glycol, and ethylene glycol, preferably isopropanol.
[0015] According to the preparation method of the present invention, in step 1), the mass ratio (g / g) of the ligand polymer to the alcohol compound is 1:(10-15).
[0016] According to the preparation method of the present invention, in step 2), the zinc salt includes one of zinc sulfate, zinc chloride, zinc acetate and zinc nitrate, preferably zinc chloride.
[0017] According to the preparation method of the present invention, in step 2),
[0018] The concentration range of the zinc salt aqueous solution is 10-30wt%;
[0019] The concentration range of the potassium hexacyanocobaltate aqueous solution is 10-30wt%;
[0020] The mass ratio (g / g) of potassium hexacyanocobaltate aqueous solution to catalyst ligand is 1:10-1:40, preferably 1:20-1:30;
[0021] The mass ratio (g / g) of the potassium hexacyanocobaltate aqueous solution to the zinc salt aqueous solution is 1:3-1:10, preferably 1:5-1:8.
[0022] According to the preparation method of the present invention, in step 2), the reaction temperature is 20-40° C., and the reaction time is 1 h to 5 h, preferably the reaction temperature is 25-35° C., and the reaction time is 2 h to 4 h.
[0023] According to the preparation method of the present invention, in step 3), the weak acid is one of lactic acid, acetic acid and formic acid, preferably acetic acid; the pH of the weak acid aqueous solution is 5-6.8, preferably 5.5-6.5.
[0024] According to the preparation method of the present invention, in step 3), the post-treatment includes drying and grinding, wherein the drying temperature is 40-60° C., and the drying time is 8 h to 24 h.
[0025] According to the preparation method of the present invention, the ligand polymer is prepared by the following steps:
[0026] S1: dissolving styrene sulfonic acid, allyl alcohol polyether and ligand polymer monomer in an organic solvent to prepare a monomer solution;
[0027] S2: adding an initiator to the monomer solution to carry out a polymerization reaction;
[0028] S3: removing the organic solvent from the reaction solution to obtain a ligand polymer.
[0029] According to the preparation method of the present invention, in step S1, the concentration of the monomer solution is 4-20wt%, preferably 5-17wt%.
[0030] According to the preparation method of the present invention, in step S1, the organic solvent is one or more of toluene, o-xylene, and m-xylene.
[0031] According to the preparation method of the present invention, in step S1, the mass ratio of styrene sulfonic acid, allyl alcohol polyether and ligand polymer monomer is 1:(1-6):(1.1-4), preferably 1:(1.05-5.5):(1.2-3.6).
[0032] According to the preparation method of the present invention, in step S1,
[0033] The structure of allyl alcohol polyether is:
[0034]
[0035] Wherein, m and n are as defined above;
[0036] The structure of the ligand polymer monomer is:
[0037]
[0038] According to the preparation method of the present invention, in step S2, the initiator is one or more of azobisisobutyronitrile, benzoyl peroxide, azobisisoheptylonitrile, and dodecanoyl peroxide, preferably azobisisobutyronitrile.
[0039] According to the preparation method of the present invention, in step S2, the amount of the initiator added is 0.15-0.30wt%, preferably 0.18-0.27wt% of the monomer solution.
[0040] According to the preparation method of the present invention, in step S2, the reaction temperature is 80-120° C., and the reaction time is 2-5 h.
[0041] According to the preparation method of the present invention, in step S3, the organic solvent in the reaction solution is removed under a vacuum condition of -0.095-0.100 MPaG, preferably at 100-120°C.
[0042] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in the following aspects:
[0043] The present invention designs and synthesizes a comb-shaped ligand polymer, introduces a stereoscopic N heterocyclic structure into the comb-shaped chain, and when forming a catalyst with zinc and cobalt, the crystallinity of the catalyst can be effectively reduced and the catalytic activity of the catalyst can be improved. At the same time, the proton acid provided by the sulfonic acid group in the ligand polymer combines with the N heterocyclic structure to form a quaternary ammonium salt cation, and the coordinated catalysis with the complex metal ion can effectively enhance the ring-opening treatment effect of ethylene oxide. The catalyst of the present invention can be used for the synthesis of high-activity castor oil polyether polyols. The primary hydroxyl content of the prepared castor oil polyol is higher than>80%, and there is no ester group chain scission, and it has the advantage of a narrow molecular weight distribution. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 The GPC spectrum of the polyether polyol prepared in Example 4 of the present invention is shown.
[0045] Figure 2 The GPC spectrum of the polyether polyol prepared in Comparative Example 1 is shown.
[0046] Figure 3 The GPC spectrum of the polyether polyol prepared in Comparative Example 2 is shown. DETAILED DESCRIPTION
[0047] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.
[0048] Unless otherwise defined, all the professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0049] Gel permeation chromatography test conditions: Waters 515 liquid chromatograph was used for testing, the chromatographic columns were HR-3, HR-4, and HR-6, the detector was a parallax detector Waters 2414, the mobile phase was tetrahydrofuran, the flow rate was 1 mL / min, the column temperature was 40°C, the sample concentration was 5 mg / mL, and narrow distribution polyethylene glycol was used as a sample.
[0050] Source of raw materials:
[0051] Unless otherwise specified, the reagents used in the examples can be purchased from reagent manufacturers, and the product purity is chemically pure.
[0052] The allyl alcohol polyether used to prepare the ligand polymer can be prepared by conventional methods. The preparation method of the allyl alcohol polyether of the present invention is described as follows.
[0053] Preparation Example 1: Preparation of Allyl Alcohol Polyether a
[0054] To a 10L reactor, 100g of allyl alcohol and 10g of metallic sodium were added. The reaction temperature was maintained at 40°C under stirring at 200rpm for 1h, and then the temperature was raised to 110°C. The flow rate was controlled to keep the pressure in the reactor less than 0.3MPaG, and 3500g of propylene oxide was continuously introduced into the reactor. The reaction was continued for 1.5h after the feeding was completed. The flow rate was controlled to keep the pressure in the reactor less than 0.3MPaG, and 2655g of ethylene oxide was continuously introduced into the reactor. The reaction was continued for 1.5h after the feeding was completed. The vacuum degree was controlled to be -0.098MPaG and the temperature was 110°C to remove unreacted propylene oxide and ethylene oxide under reduced pressure. 50.2 phosphoric acid and 300g of water were added to the reaction solution for neutralization for 1h, 3g of adsorbent was added for adsorption for 1h, dehydrated to a moisture content of less than 0.05%, and filtered to obtain allyl alcohol polyether a (m=25, n=25).
[0055] According to the same preparation method as in Preparation Example 1, allyl alcohol polyether b of Preparation Example 2 and allyl alcohol polyether c of Preparation Example 3 were obtained, wherein the reaction conditions were the same as in Preparation Example 1, except for the feed ratio. The feed amounts of allyl alcohol polyether b and allyl alcohol polyether c are shown in Table 1 below.
[0056] Table 1
[0057] Allyl alcohol(g) Sodium metal (g) Propylene oxide(g) Ethylene oxide (g) Phosphoric acid(g) Water(g) Allyl alcohol polyether b 100 10 5000 379 50.2 300 Allyl alcohol polyether c 100 10 7500 1137 50.2 300
[0058] The structure of the prepared allyl alcohol polyether b is m=5, n=50; the structure of the prepared allyl alcohol polyether c is m=15, n=75.
[0059] The following examples use ligand polymer monomer A to prepare ligand polymers, which can be prepared with reference to patent CN 111440180B. The structure of ligand polymer monomer A is as follows:
[0060]
[0061] Example
[0062] Example 1 Preparation of Catalyst A
[0063] Synthesis of ligand polymer a: 50 g of styrene sulfonic acid, 90.7 g of allyl alcohol polyether a, and 90 g of monomer A were dissolved in 800 g of toluene to prepare a solution, 2.70 g of azobisisobutyronitrile was added to the solution, the temperature was raised to 100°C under stirring at 500 rpm, and the reaction was continued at 100°C for 3 h. The vacuum degree was controlled to be -0.098 MPaG and the temperature was 100°C to remove toluene from the reaction solution. The product was placed in a dialysis bag for dialysis purification, and the vacuum degree was controlled to be -0.098 MPaG and the temperature was 100°C to remove moisture from the purified product to obtain ligand polymer a (gel permeation chromatography test showed a number average molecular weight of 34200, PDI of 1.46, m=25, n=25, a:b:c=10:1:10).
[0064] 10g of ligand polymer a and 100g of isopropanol were stirred and mixed to obtain a catalyst ligand; the catalyst ligand and 5g of potassium hexacyanocobaltate aqueous solution (30wt%) were simultaneously added dropwise to 15g of zinc chloride aqueous solution (30wt%) under stirring conditions, and the addition took 1 hour to complete. After the addition was completed, stirring and reacting were continued for 1 hour. The temperature of this process was maintained at 20°C throughout the whole process. After the reaction was completed, a solid precipitate was filtered to obtain a crude catalyst product; the crude catalyst product was washed three times with 500mL of acetic acid aqueous solution with a pH of 5, filtered to remove water after washing, and then dried in a vacuum environment at 40°C for 24 hours, taken out and ground to obtain a catalyst product a.
[0065] Example 2 Preparation of Catalyst B
[0066] Synthesis of ligand polymer b: 50g of styrene sulfonic acid, 53g of allyl alcohol polyether b, and 178g of monomer A were dissolved in 800g of m-xylene to form a solution, 1.9g of azobisisobutyronitrile was added to the solution, the temperature was raised to 100°C under stirring at 500rpm, and the reaction was continued at 100°C for 3h. The vacuum degree was controlled to be -0.098MPaG and the temperature was 100°C to remove the m-xylene in the reaction solution. The product was placed in a dialysis bag for dialysis purification, and the vacuum degree was controlled to be -0.098MPaG and the temperature was 100°C to remove the water in the purified product to obtain ligand polymer b (gel permeation chromatography test number average molecular weight is 35600, PDI is 1.39, m=5, n=50, a:b:c=15:1:30).
[0067] 100 g of ligand polymer b and 1200 g of propylene glycol were stirred and mixed to obtain catalyst ligand b; catalyst ligand b and 51 g of potassium hexacyanocobaltate aqueous solution (10 wt%) were simultaneously added dropwise to 510 g of zinc sulfate aqueous solution (10 wt%) under stirring conditions, and the addition took 1 hour to complete. After the addition was completed, stirring and reacting were continued for 5 hours. The temperature was maintained at 40° C. throughout the process. After the reaction was completed, a solid precipitate was obtained by filtration, which was a crude catalyst product; the crude catalyst product was washed three times with 2000 mL of lactic acid aqueous solution with a pH of 6.8, filtered to remove water after washing, and then dried in a vacuum environment at 60° C. for 8 hours, taken out and ground to obtain catalyst product b.
[0068] Example 3 Preparation of Catalyst C
[0069] Synthesis of ligand polymer c: 50 g of styrene sulfonic acid, 268 g of allyl alcohol polyether c, and 63 g of monomer A were dissolved in 800 g of toluene to prepare a solution, 3.2 g of azobisisobutyronitrile was added to the solution, the temperature was raised to 100°C under stirring at 500 rpm, and the reaction was continued at 100°C for 3 h. The vacuum degree was controlled to be -0.098 MPaG and the temperature was 100°C to remove the toluene in the reaction solution. The product was placed in a dialysis bag for dialysis purification, and the vacuum degree was controlled to be -0.098 MPaG and the temperature was 100°C to remove the moisture in the purified product to obtain ligand polymer c (gel permeation chromatography test number average molecular weight is 35600, PDI is 1.39, m=15, n=75, a:b:c=20:1:60).
[0070] 10g of ligand polymer c and 150g of tert-butanol were stirred and mixed to obtain a catalyst ligand; the catalyst ligand and 5.3g of potassium hexacyanocobaltate aqueous solution (20wt%) were simultaneously added dropwise to 32g of zinc nitrate aqueous solution (20wt%) under stirring conditions, and the addition took 1 hour to complete. After the addition was completed, stirring and reacting were continued for 3 hours. The temperature of this process was maintained at 30°C throughout the whole process. After the reaction was completed, a solid precipitate was filtered to obtain a crude catalyst product; the crude catalyst product was washed three times with 1000mL of formic acid aqueous solution with a pH of 6, filtered to remove water after washing, and then dried in a vacuum environment at 50°C for 12 hours, taken out and ground to obtain a catalyst product c.
[0071] Example 4 Synthesis of polyether polyols
[0072] 900g of castor oil was used as an initiator and mixed with 0.10g of the catalyst a in the above embodiment, the temperature was raised to 100°C, and the mixture was stirred until the materials were uniformly dispersed. The temperature was maintained at 100°C, and the mixture was stirred and dehydrated for 2h under a vacuum environment; the temperature was raised to 140°C, and 50g of propylene oxide was added for activation; when the pressure dropped to -0.09MPaG, 1900g of propylene oxide was continuously added to the reaction vessel again, the reaction temperature was controlled to be 140°C during the reaction, and the pressure was not higher than 0.3MPaG. After the feeding was completed, the reaction was continued for 30min, nitrogen was filled into the reactor until the pressure rose to 0.1MPaG, 450g of ethylene oxide was continuously added to the reaction vessel again, the reaction temperature was controlled to be 140°C during the reaction, and the pressure was not higher than 0.3MPaG. After the feeding was completed, the reaction was continued for 30min, and then the vacuum degree was controlled to be -0.098MPaG and the temperature was 140°C to remove unreacted ethylene oxide under reduced pressure to obtain 3000g of polyether polyol product.
[0073] Example 5 Synthesis of polyether polyols
[0074] The difference from Example 4 is that the catalyst b in Example 2 is used, and the other conditions are the same. The GPC spectrum of the polyether polyol prepared in Example 5 is consistent with that of Example 4.
[0075] Example 6 Synthesis of polyether polyols
[0076] The difference from Example 4 is that the catalyst c in Example 3 is used, and the other conditions are the same. The GPC spectrum of the polyether polyol prepared in Example 6 is consistent with that of Example 4.
[0077] Comparative Example 1 Synthesis of polyether polyol
[0078] The difference from Example 4 is that KOH is used as a catalyst, the catalyst amount is 18 g, and the other conditions are the same.
[0079] Comparative Example 2 Synthesis of polyether polyol
[0080] The difference from Example 4 is that the bimetallic catalyst used in the preparation of polyether polyol in this comparative example is a commercially available product of Huaian Bader Polyurethane Technology Co., Ltd., and the other conditions are the same.
[0081] The polyether polyols prepared in Examples 4-6 and the polyether polyols prepared in Comparative Examples 1 and 2 were tested for hydroxyl value, viscosity and appearance with reference to GB / T12008.3-2009 Plastic Polyether Polyols. The molecular weight distribution of the samples was tested by gel permeation chromatography, and the primary hydroxyl content of the samples was tested by nuclear magnetic resonance. The results are shown in Table 2.
[0082] Table 2
[0083]
[0084]
[0085] From the test data in Table 2, it can be seen that the molecular weight distribution of the samples of Examples 4-6 is about 1.18, and the primary hydroxyl content is about 84%. Compared with Comparative Example 1, the molecular weight distribution of the samples of the examples is significantly smaller than that of the samples of Comparative Example 1, which can prove that the ester group has no breakage. Compared with Comparative Examples 1 and 2, the primary hydroxyl content of the samples of the examples is significantly higher than that of the samples of Comparative Examples 1 and 2, which proves that the catalyst of the present invention is suitable for the polymerization of EO and can produce products with high primary hydroxyl content. The catalyst of the present invention can be used for the synthesis of high-activity castor oil polyether polyols. The primary hydroxyl content of the castor oil polyols produced is higher than>80%, and there is no ester group chain breakage, which has the advantage of narrow molecular weight distribution.
Claims
1. A method for preparing a catalyst for the synthesis of highly active bio-based polyols, The following steps are involved: 1) mixing the ligand polymer and the alcohol compound to obtain a catalyst ligand; 2) the catalyst ligand obtained in step 1) and the potassium hexacyanocobaltate aqueous solution are simultaneously and slowly added dropwise to the zinc salt aqueous solution to react, and a solid precipitate is obtained as a crude catalyst; 3) The crude catalyst is washed with a weak acid aqueous solution, then washed with desalted water, filtered to remove water, and then post-processed to obtain the catalyst.
2. The preparation method according to claim 1, in, In step 1), the structure of the ligand polymer is: Among them, a:b=10:1-20:1, a:c=1:1-1:3, 50≤m+n≤100, m:n=1:1-1:
10.
3. The preparation method according to claim 1 or 2, in, In step 1), The alcohol compound is one or more of isopropanol, tert-butyl alcohol, propylene glycol, and ethylene glycol; The mass ratio of the ligand polymer to the alcohol compound is 1:(10-15).
4. The preparation method according to any one of claims 1 to 3, in, In step 2), The zinc salt includes one of zinc sulfate, zinc chloride, zinc acetate and zinc nitrate; The concentration range of the zinc salt aqueous solution is 10-30wt%; The concentration range of the potassium hexacyanocobaltate aqueous solution is 10-30wt%; The mass ratio of potassium hexacyanocobaltate aqueous solution to catalyst ligand is 1:10-1:40, preferably 1:20-1:30; The mass ratio of the potassium hexacyanocobaltate aqueous solution to the zinc salt aqueous solution is 1:3-1:10, preferably 1:5-1:8; The reaction temperature is 20-40°C, and the reaction time is 1h-5h.
5. The preparation method according to any one of claims 1 to 4, in, In step 3), The weak acid is one of lactic acid, acetic acid and formic acid; the pH of the weak acid aqueous solution is 5-6.8; The post-processing includes drying and grinding, wherein the drying temperature is 40-60°C and the drying time is 8h-24h.
6. The preparation method according to any one of claims 1 to 5, in, The ligand polymer is prepared by the following steps: S1: dissolving styrene sulfonic acid, allyl alcohol polyether and ligand polymer monomer in an organic solvent to prepare a monomer solution; S2: adding an initiator to the monomer solution to carry out a polymerization reaction; S3: removing the organic solvent from the reaction solution to obtain a ligand polymer.
7. The preparation method according to claim 6, in, In step S1, The concentration of the monomer solution is 4-20wt%; The organic solvent is one or more of toluene, o-xylene, and m-xylene; The mass ratio of styrene sulfonic acid, allyl alcohol polyether and ligand polymer monomer is 1:(1-6):(1.1-4).
8. The preparation method according to claim 6 or 7, in, In step S1, The structure of allyl alcohol polyether is: wherein m and n are as defined in claim 2; The structure of the ligand polymer monomer is:
9. The preparation method according to any one of claims 6 to 8, in, In step S2, The initiator is one or more of azobisisobutyronitrile, benzoyl peroxide, azobisisoheptanenitrile, and dodecanoyl peroxide; The amount of the initiator added is 0.15-0.30wt% of the monomer solution; The reaction temperature is 80-120°C and the reaction time is 2-5h.
10. The preparation method according to any one of claims 6 to 9, in, In step S3, the organic solvent in the reaction solution is removed under a vacuum condition of -0.095-0.100 MPaG.
Citation Information
Patent Citations
Polyether polyol, preparation method thereof, and polyurethane foam
CN110054767A
Polyether polyol containing carbamate structure as well as synthesis method and application of polyether polyol
CN115785431A
Process for preparing a polyoxyalkylene carbonate polyol
US20230174705A1
Biobased-petrochemical hybrid polyols
US8692030B1
Cited By
A cobalt potassium cyanide composition and method of preparation and use thereof
CN122704950A
